Impact of the 2022 Interest-Rate Shock on Cooperative Banks in Germany: A Case Study - Andreas Bley (Vierteljahrshefte zur Wirtschaftsforschung, 2023)
Between July and December 2022, the European Central Bank (ECB) raised its key interest rate by a very substantial 250 basis points. This interest-rate shock presented the German cooperative banks as well as many other credit institutions with huge challenges. The cooperative banks suffered a significant hit to their income, mainly in the form of high fair value losses in securities portfolios following the interest-rate shock and, to a much lesser extent, in a deterioration of fair value gains and losses in the lending business due to the faltering economy. Nonetheless, the cooperative banks delivered a strong operating performance and strengthened their capital base. Over the medium term, the return to positive interest rates should create a tailwind for financial performance. In the coming years, reversals of impairment losses should generate favorable effects as most securities are held to maturity. A key factor for future operating performance will be the trajectory of capital investment in Germany going forward. – – Zwischen Juli und Dezember erhöhte die Europäische Zentralbank (EZB) ihren Leitzins äußerst kräftig um 250 Basispunkte. Dieser Zinsschock stellte für die deutschen Genossenschaftsbanken wie auch für viele andere Kreditinstitute eine große Herausforderung dar. Infolgedessen mussten die Genossenschaftsbanken deutliche Ertragseinbußen hinnehmen. Diese äußerten sich überwiegend in einem hohen Bewertungsaufwand in den Wertpapierportfolien infolge des Zinsschocks und zu einem deutlich geringeren Teil im Bewertungsergebnis des Kreditgeschäfts angesichts der sich abschwächenden Konjunktur. Dennoch konnte operativ ein gutes Ergebnis erzielt und zusätzliches Eigenkapital aufgebaut werden. Mittelfristig dürfte die Rückkehr zu positiven Zinsen die Ertragslage deutlich verbessern. In den kommenden Jahren sind positive Effekte durch Wertaufholungen zu erwarten, da ein Großteil der Wertpapiere bis zur Endfälligkeit gehalten wird. Wichtig für die kommende operative Ertragsentwicklung ist die Frage, wie sich die Investitionstätigkeit in Deutschland perspektivisch entwickeln wird.
Keywords: G01; G21; E58; 330; cooperative banks; financial crises; central banks and their policies